HipA-Mediated Phosphorylation of SeqA Does not Affect Replication Initiation in Escherichia coli - Riber, Leise; Koch, Birgit M.; Kruse, Line Riis; Germain, Elsa; Løbner-Olesen, Anders (Frontiers in Microbiology, 2018)
The SeqA protein of Escherichia coli is required to prevent immediate re-initiation of chromosome replication from oriC. The SeqA protein is phosphorylated at the serine-36 (Ser36) residue by the HipA kinase. The role of phosphorylation was addressed by mutating the Ser36 residue to alanine, which cannot be phosphorylated and to aspartic acid, which mimics a phosphorylated serine residue. Both mutant strains were similar to wild-type with respect to origin concentration and initiation synchrony. The minimal time between successive initiations was also unchanged. We therefore suggest that SeqA phosphorylation at the Ser36 residue is silent, at least with respect to SeqA’s role in replication initiation.